2013
DOI: 10.1002/ceat.201200537
|View full text |Cite
|
Sign up to set email alerts
|

Methane Hydrate Formation and Dissociation in the presence of Bentonite Clay Suspension

Abstract: The present work reports the effect of bentonite clay on methane hydrate formation and dissociation in synthetic seawater of salinity 3.55 % of total dissolved salts. Extensive observations of pressure-temperature equilibrium during formation and decomposition of methane hydrate under different conditions have been made. It is observed that phase equilibrium conditions of hydrate are affected on changing the concentration of bentonite clay in synthetic seawater. Induction time for hydrate nucleation has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…It is known that the mineral surface can facilitate hydrate crystallization and stabilize the hydrate cages by providing nucleation sites. 5,6 Nevertheless, scientific knowledge remains incomplete about the intercalation of NGH in the clay mineral interlayers, because the hydrate formation varied against the surface hydrophobicity, 7 surface charge, 8 surface area, 9 pore size distribution, 10 and particle size and chemical compositions of minerals. 11 Moreover, it becomes more complicated when natural soil organic matter (e.g., humic substances, lignins, and compounds with amide and amine groups) is present in the clays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the mineral surface can facilitate hydrate crystallization and stabilize the hydrate cages by providing nucleation sites. 5,6 Nevertheless, scientific knowledge remains incomplete about the intercalation of NGH in the clay mineral interlayers, because the hydrate formation varied against the surface hydrophobicity, 7 surface charge, 8 surface area, 9 pore size distribution, 10 and particle size and chemical compositions of minerals. 11 Moreover, it becomes more complicated when natural soil organic matter (e.g., humic substances, lignins, and compounds with amide and amine groups) is present in the clays.…”
Section: Introductionmentioning
confidence: 99%
“…Geochemical data further indicated that smectite, a group of 2:1 clay minerals, such as sodium montmorillonite (Na-MMT), was the most abundant mineral in the oceanic hydrate-bearing sediments. , Therefore, there are increasing investigations to explore the interactions between gas hydrate and clay minerals. It is known that the mineral surface can facilitate hydrate crystallization and stabilize the hydrate cages by providing nucleation sites. , Nevertheless, scientific knowledge remains incomplete about the intercalation of NGH in the clay mineral interlayers, because the hydrate formation varied against the surface hydrophobicity, surface charge, surface area, pore size distribution, and particle size and chemical compositions of minerals …”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the induction time is defined as the time taken from the start of the experiment to the initiation of hydrate nucleation 37. The induction time can be defined as in the following equation: trueInduction time= t0 - tnormals …”
Section: Calculation Proceduresmentioning
confidence: 99%
“…Beyond the well-established factors such as hydrate saturation and stress conditions, it can be significantly altered by the pattern of hydrate accumulation. Figure 1 illustrates the mesoscale distribution patterns of hydrates in three prevalent sediment structures: the filling pattern, the skeleton pattern, and the bonding pattern [31,32]. For this study, the hydrate accumulation pattern is of paramount importance.…”
Section: Particle Contact Modelmentioning
confidence: 99%